Case Report on Pseudoaneurysm of Brachial Artery: A Rare Complication of Paediatric Supracondylar Humerus Fracture Pinning - Bhandari, Prawesh S; Bastola, Priska; Gurung, Dinesh (Journal of Institute of Medicine Nepal, 2019)
Pseudoaneurysm (PA) of the brachial artery in pediatric supracondylar humerus fracture who have undergone closed reduction and percutaneous pinning is a rare complication. A few cases have been reported in medical literature. This case report sheds some insight into early identification and management outcome of such complication. Rapidly progressive swelling in antecubital fossa in cases of supracondylar fracture who have undergone pinning should arouse suspicion of vascular lesion. It should be timely intervened. Surgical intervention of pseudoaneurysm with reversed saphenous venous graft has shown to have no early vascular complication.